2017
DOI: 10.1016/j.ajog.2017.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Sexual function in infertile women with polycystic ovary syndrome and unexplained infertility

Abstract: Background While female sexual dysfunction is a frequent occurrence, characteristics in infertile women are not well delineated. Furthermore, the impact of infertility etiology on the characteristics in women with differing androgen levels observed in women with polycystic ovary syndrome and unexplained infertility has not been assessed. Objective To determine the characteristics of sexual dysfunction in women with polycystic ovary syndrome and unexplained infertility. Study Design Secondary data analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 33 publications
2
38
0
Order By: Relevance
“…Among them, 11 studies were excluded for lacking a control group; six studies did not meet the inclusion criteria; four studies for inappropriate grouping; five studies for insufficient outcome data; and three studies for previous publications. In all, 10 relevant studies (Drosdzol et al, 2007;Battaglia et al, 2008;Stovall et al, 2012;Ercan et al, 2013;Ferraresi et al, 2013;Benetti-Pinto et al, 2015;Lara et al, 2015;Zueff et al, 2015;Diamond et al, 2017;Noroozzadeh et al, 2017b) met our pre-defined eligibility criteria, and were included in the present study. The selection process is presented in FIGURE 1.…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, 11 studies were excluded for lacking a control group; six studies did not meet the inclusion criteria; four studies for inappropriate grouping; five studies for insufficient outcome data; and three studies for previous publications. In all, 10 relevant studies (Drosdzol et al, 2007;Battaglia et al, 2008;Stovall et al, 2012;Ercan et al, 2013;Ferraresi et al, 2013;Benetti-Pinto et al, 2015;Lara et al, 2015;Zueff et al, 2015;Diamond et al, 2017;Noroozzadeh et al, 2017b) met our pre-defined eligibility criteria, and were included in the present study. The selection process is presented in FIGURE 1.…”
Section: Literature Searchmentioning
confidence: 99%
“…A total of 2626 participants with a mean age range between 25 and 36 years were enrolled, 1163 of whom were women with PCOS whereas the remaining 1463 women were healthy individuals. Six studies (Stovall et al, 2012;Ferraresi et al, 2013;Benetti-Pinto et al, 2015;Lara et al, 2015;Zueff et al, 2015;Diamond et al, 2017) were conducted in America, three studies (Drosdzol et al, 2007;Battaglia et al, 2008;Ercan et al, 2013) in Europe, and one study (Noroozzadeh et al, 2017b) FIGURE 1 Study selection. The two included studies that provided the mean total FSFI scores and the total cases of the study group and control group but did not report the number of FSD cases:…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial data demonstrate decreased health‐related quality of life in women with PCOS . Moreover, several recent studies have demonstrated increased frequency of both depression and anxiety in these women . However, little data exist regarding eating patterns and attitudes or potential comorbid eating disorders in women with PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Moreover, several recent studies have demonstrated increased frequency of both depression and anxiety in these women. 15,16 However, little data exist regarding eating patterns and attitudes or potential comorbid eating disorders in women with PCOS. Studies have reported an increased frequency of PCOS among women with anorexia nervosa or bulimia nervosa, but these results have not been substantiated in large cross-sectional studies.…”
mentioning
confidence: 99%